Acute kidney injury in patients hospitalized with COVID-19 from the ISARIC WHO CCP-UK Study: a prospective, multicentre cohort study. Issue 2 (18th October 2021) - Sullivan, Michael K; Lees, Jennifer S; Drake, Thomas M; Docherty, Annemarie B; Oates, Georgia; Hardwick, Hayley E; Russell, Clark D; Merson, Laura; Dunning, Jake; Nguyen-Van-Tam, Jonathan S; Openshaw, Peter; Harrison, Ewen M; et al.
ABSTRACT: Background: Acute kidney injury (AKI) is common in coronavirus disease 2019 (COVID-19). This study investigated adults hospitalized with COVID-19 and hypothesized that risk factors for AKI would include comorbidities and non-White race. Methods: A prospective multicentre cohort study was performed using patients admitted to 254 UK hospitals with COVID-19 between 17 January 2020 and 5 December 2020. Results: Of 85 687 patients, 2198 (2.6%) received acute kidney replacement therapy (KRT). Of 41 294 patients with biochemistry data, 13 000 (31.5%) had biochemical AKI: 8562 stage 1 (65.9%), 2609 stage 2 (20.1%) and 1829 stage 3 (14.1%). The main risk factors for KRT were chronic kidney disease (CKD) [adjusted odds ratio (aOR) 3.41: 95% confidence interval 3.06–3.81], male sex (aOR 2.43: 2.18–2.71) and Black race (aOR 2.17: 1.79–2.63). The main risk factors for biochemical AKI were admission respiratory rate >30 breaths per minute (aOR 1.68: 1.56–1.81), CKD (aOR 1.66: 1.57–1.76) and Black race (aOR 1.44: 1.28–1.61). There was a gradated rise in the risk of 28-day mortality by increasing severity of AKI: stage 1 aOR 1.58 (1.49–1.67), stage 2 aOR 2.41 (2.20–2.64), stage 3 aOR 3.50 (3.14–3.91) and KRT aOR 3.06 (2.75–3.39). AKI rates peaked in April 2020 and the subsequent fall in rates could not be explained by the use of dexamethasone or remdesivir. Conclusions: AKI is common in adults hospitalized with COVID-19 and it is associated with a heightened risk of mortality. Although the rates of AKI have fallen from the early months of the pandemic, high-risk patients should have their kidney function and fluid status monitored closely. Graphical Abstract: